Incidence and risk factors of delirium in surgical intensive care unit. Issue 1 (3rd March 2021) - Ali, Muhammad Asghar; Hashmi, Madiha; Ahmed, Waqas; Raza, Syed Amir; Khan, Muhammad Faisal; Salim, Bushra
Abstract : Background: To evaluate the incidence and modifiable risk factors of delirium in surgical intensive care unit (SICU) of tertiary care hospital in a low-income and middle-income country. Methods: We conducted a single cohort observational study in patients over 18 years of age who were admitted to the SICU for >24 hours in Aga Khan University Hospital from January to December 2016. Patients who had pre-existing cognitive dysfunction were excluded. Intensive Care Delirium Screening Checklist was used to assess delirium. Incidence of delirium was computed, and univariate and multivariable analyses were performed to observe the relationship between outcome and associated factors. Results: The average patient age was 43.29±17.38 and body mass index was 26.25±3.57 kg/m 2 . Delirium was observed in 19 of 87 patients with an incidence rate of 21.8%. Multivariable analysis showed chronic obstructive pulmonary disease, pain score >4 and hypernatremia were strong predictors of delirium. Midazolam (adjusted OR (aOR)=7.37; 95% CI 2.04 to 26.61) and propofol exposure (aOR=7.02; 95% CI 1.92 to 25.76) were the strongest independent predictors of delirium while analgesic exposures were not statistically significant to predict delirium in multivariable analysis. Conclusion: Delirium is a significant risk factor of poor outcome in SICU. There was an independent association between pain, sedation, COPD, hypernatremia and fever in developing delirium. Level of evidence: IV.